Deposit Mobilization and Profitability in Nepalese Commercial Banks - Gnawali, Bindu; Niroula, Ballav (Jurnal Studi Manajemen dan Bisnis, 2024)
A commercial bank must be able to receive deposits at reasonable rates to have funds available to lend to its customers. Therefore, if all other variables stay the same, a bank that can attract more deposits will be able to make more profit. The main objective of this research is to show the impact of deposit mobilization on the profitability of Nepalese commercial banks. The secondary panel data from 2015 to 2023 were collected from the annual report of commercial banks using the purposive sampling method. Casual comparative research design has been used to analyze and interpret the data. The collected data were described and analyzed using Ms. Excel and SPSS version 25 software. The findings of the study revealed that there is a significant and positive effect of IRS and IOD on return on assets but inflation has a significant negative effect. Similarly, IRS and IOD have a significant and positive impact on return on assets. However, inflation has a significant negative effect. Interest rate spread and interest on deposits are the major elements of banks to maximize their profitability.